Biophysical modifications during the El Niño phenomenon and correlation with encephalitis virus epidemic in Talara, Peru 1997-1998 - Briceño Aliaga, Mónica (2016)
El Niño occurs every 4 to 7 years; It is part of an atmospheric ocean natural event known as ENSO (El Niño-Southern Oscillation). Under normal conditions, on the west side of the Pacific Ocean there is a sea temperature of 29 ° C and a system of low atmospheric pressure in Darwin Australia; while on the east side there is a high pressure system in Papeete-Tahiti and level the coasts of Peru and Ecuador, where the sea temperature is 19 to 23 ° C. The cold waters of the eastern Pacific condition in the atmosphere high pressure zones and the warm waters of low pressure zones; the pressure difference causes the trade winds traveling from east to west, dragging surface waters and producing an upwelling phenomenon, whereby, the colder waters of the sea bottom out at the surface. The deep waters are rich in salts and micronutrients for the formation of phytoplankton base of the food chain in fish. Phytoplankton live in the illuminated upper layers; It is important in the processes of ocean-atmospheric interaction modulates heat production dimethyl sulfide (DMS); influence ocean chemistry using carbon dioxide dissolved in water to produce sugar and oxygen. It uses inorganic nutrients such as nitrogen, phosphorus, silicon, iron to synthesize complex molecules such as proteins.